Factors affecting milk quality of crossbred dairy cows in automated Herringbone milking system - FAHIM, A; KAMBOJ, M L; SIROHI, A S; BHAKAT, M; MOHANTY, T K (The Indian Journal of Animal Sciences, 2017)
The aim of the study was to investigate the effect of factors affecting milk quality of crossbred dairy cows milked in automated Herringbone milking system. The study was conducted on 37 crossbred Karan Fries cows of different parities, stages of lactation and udder types for 3 months. The milk quality was assessed based on milk composition, on-line electrical conductivity (EC) and peak conductivity, somatic cell count (SCC) and standard plate count (SPC) of milk samples. The results showed that there was no change in milk composition in terms of fat and SNF except in different parity groups. The milk conductivity was significantly higher in the late stage of lactation. However, no change in SCC values was observed. The udder types showed significant increase in EC values in udders with poor structure and loose attachment. The SCC values were also significantly higher for such udder types. The SPC was significantly higher when the number of milkings on each liner exceeded 2000 milkings/liner. The SCC was had a positive correlation with EC and SPC. The correlation between SPC and SCC was highly significant whereas, EC was moderately correlated with SPC. It can be concluded that the milk quality of crossbred dairy cows was significantly affected by parity, stages of lactation, udder type and liner usage in automated parlours. Therefore, effective management strategy needs to be taken to improve the quality of milk taking into consideration on-line EC, SCC and SPC.